The use of ICT tools in the Teaching-Learning process of English and French in the fifthyear students of the B.A in Modern Languages: specialty in French and English at the Foreign Language Department, School of Arts and Sciences, University of El Salvador in the year 2019. - Anaya Pineda, Gricelda Maribel; Nieto Carranza, Rosa Carolina; Blanco Martínez, María Fernanda (2024)
¨The use of ICT tools in the Teaching-Learning process of English and French in the fifth-year students of the B.A in Modern Languages: specialty in French and English at the Foreign Language Department, School of Arts and Sciences, University of El Salvador in the year 2019.¨ Technology facilitates daily events for individuals; educational field is not the exception. The aim of this research is to detect the most common ICT tools used in the teaching-learning process of English and French in the fifth-year students of Modern Languages B.A, its benefits and to discover how teachers and students implement them. To gather data, a questionnaire was distributed to students on the fifth-year of Modern Languages bachelor in the 2019 year. In addition, a structured interview was addressed to the English and French teachers of the Foreign Language Department. The data was analyzed using descriptive analysis and mixed methods were applied in this research. The results reveal the most common tools used and how teachers have reinvented themselves and play new virtual strategies that emphasized on catching learners' attention keeps students focused on the information transmitted. To nurture the TeachingLearning process of English and French in the fifth-year students of Modern Languages the FLD of the University of El Salvador can use this research in everyday courses. Key words: ICT ; Teaching-Learning process ; Education ; eLearning ; Advanced technology ; innovative ; Interactive material ; Traditional teaching methods ; Effectiveness ; Social networks ; Apps ; Platforms ; Macro skills ; Budgets ; Internet connection ; Physical environment ; New reality ; Training ; Equipment.